Prevalence and causes of blindness and vision impairment: magnitude, temporal trends and projections in South and Central Asia. Issue 7 (8th November 2018) - Nangia, Vinay; Jonas, Jost B; George, Ronnie; Lingam, Vijaya; Ellwein, Leon; Cicinelli, Maria Vittoria; Das, Aditi; Flaxman, Seth R; Keeffe, Jill E; Kempen, John H; Leasher, Janet; Limburg, Hans; et al.
Abstract : Background: To assess prevalence and causes of vision loss in Central and South Asia. Methods: A systematic review of medical literature assessed the prevalence of blindness (presenting visual acuity<3/60 in the better eye), moderate and severe vision impairment (MSVI; presenting visual acuity <6/18 but ≥3/60) and mild vision impairment (MVI; presenting visual acuity <6/12 and ≥6/18) in Central and South Asia for 1990, 2010, 2015 and 2020. Results: In Central and South Asia combined, age-standardised prevalences of blindness, MSVI and MVI in 2015 were for men and women aged 50+years, 3.72% (80% uncertainty interval (UI): 1.39–6.75) and 4.00% (80% UI: 1.41–7.39), 16.33% (80% UI: 8.55–25.47) and 17.65% (80% UI: 9.00–27.62), 11.70% (80% UI: 4.70–20.32) and 12.25% (80% UI:4.86–21.30), respectively, with a significant decrease in the study period for both gender. In South Asia in 2015, 11.76 million individuals (32.65% of the global blindness figure) were blind and 61.19 million individuals (28.3% of the global total) had MSVI. From 1990 to 2015, cataract (accounting for 36.58% of all cases with blindness in 2015) was the most common cause of blindness, followed by undercorrected refractive error (36.43%), glaucoma (5.81%), age-related macular degeneration (2.44%), corneal diseases (2.43%), diabetic retinopathy (0.16%) and trachoma (0.04%). For MSVI in South Asia 2015, most common causes were undercorrected refractive error (accounting for 66.39% of all cases with MSVI), followed by cataract (23.62%), age-related macular degeneration (1.31%) and glaucoma (1.09%). Conclusions: One-third of the global blind resided in South Asia in 2015, although the age-standardised prevalence of blindness and MSVI decreased significantly between 1990 and 2015.